Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) clones from Paraguayan children - Fátima Rodriguez; Claudia Salinas; Silvina Fernandez; Sol Haim; Marta Mollerach; Wilma Basualdo; Hector Castro; Beatriz Quiñónez; Rocio Arguello; Monica Rodriguez; Lorena Grau; Carmen Espínola; et al. (Journal of Infection in Developing Countries)
Introduction: Staphylococcus aureus is considered one of the most important human pathogens, and its levels of resistance to methicillin have increased even in strains isolated from people without nosocomial risk factors. Molecular analysis is essential for understanding the patterns of dissemination. The objective of this study was to identify community-acquired methicillin-resistant S. aureus (CA-MRSA) clones that infected Paraguayan children patients in two periods of time.